Modeling and Simulation in Cancer Nanomedicine - Talukdar, Keka (Journal of Basic & Applied Sciences, 2021)
There is a certain function of ion channels in cancer cell progression and proliferation. The mutation of ion channels is proved to have a clear influence on the same. The progress of nanomedicine research needs the proper concept of the exact role of ion channels in cancer and the cause of the disease. In this work, an ion channel protein residing in our stomach with PDB id 3ux4 is analyzed to get an idea about its structure-function relationship. The disordered region and mutation sensitivity of the channel causing cancer are analyzed in different ways. Eight disordered regions of the protein are found in the study. The pocket in the active site is found along with the position of the miss-sense mutation. The maximum mutation region is also found for a sample disordered region. The engineered ion channel is simulated in the environment of water and ions. The potential energy of the water-ion model of the protein calculated by molecular dynamics simulation is 20,412 kcal/mol after simulating the system for 1,00000 steps.